Landscape assessment of the availability of medical abortion medicines in India - Priya Karna; K. Aparna Sharma; Amy Grossman; Madhur Gupta; Tapas Chatterjee; Natalie Williams; Ndola Prata; Annik Sorhaindo; Laurence Läser; Ulrika Rehnström Loi; Bela Ganatra; Pushpa Chaudhary (BMC, 2024)
Abstract Background Medical abortion with mifepristone and misoprostol can be provided up to 63 days' gestation in India. This accounts for 67.5 percent of all abortions in the country. We conducted an assessment to determine the availability of medical abortion medicines, specifically the combi-pack, in India. Methods We applied the World Health Organization landscape assessment protocol at the national level. The assessment protocol included a five-step adaptation of an existing availability framework, including online data collection, desk review, country-level key informant interviews, and an analysis to identify barriers and opportunities to improve medical abortion availability. The assessment was conducted between August and March 2021. Results Medicines for medical abortion are included in the national essential drug list and available with prescription in India. The assessment identified 42 combi-pack products developed by 35 manufacturers. The quality of medical abortion medicines is regulated by national authorities; but as health is devolved to states, there are significant inter-state variations. This is seen across financing, procurement, manufacturing, and monitoring mechanisms for quality assurance of medical abortion medicines prior to distribution. There is a need to strengthen supply chain systems, ensure consistent availability of trained providers and build community awareness on use of medical abortion medicines for early abortions, at the time of the assessment. Conclusion Opportunities to improve availability and quality of medical abortion medicines exist. For example, uniform implementation of regulatory standards, greater emphasis on quality-assurance during manufacturing, and standardizing of procurement and supply chain systems across states. Regular in-service training of providers on medical abortion is required. Finally, innovations in evidence dissemination and community engagement about the recently amended abortion law are needed.